ANALISIS STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DALAM FENOMENA BOTTLE-NECK PAMEN POLRI - Wijaya, Chairul Ridha, Chandra (Jurnal Ilmu Administrasi Negara, 2020)
Analysis of Human Resource Management Strategies in the Police Pamen Bottle-Neck Phenomenon. Polri is a civil servant institution in Indonesia in which committed toward personnel’s competency. This commitment included to the issue of personnel’s replacement to a position matched with their capability and capacity. However, this commitment is not easily exe-cuted nowadays due to bottle-neck phenomenon in which caused stacking of position’s queue for personnel with Police Senior Superintendent rank. This research is qualitative in nature. This re-search will describe the HR Management in Polri as an institution and also the bottle-neck phe-nomenon that happen nowadays. This research founds that bottle-neck phenomenon is caused by poor HR planning in the past, in which also caused the stacking of position’s queue in Polri nowa-days.